Model Pengelolaan Sumber Daya Laut dan Pesisir di Negeri Hitu, Kecamatan Leihitu, Kabupaten Maluku Tengah - Angga, La Ode; Ruslan, Dyah Auliah Rachma; Baharuddin, Wahdaniah; Akyuwen, Rory Jeff (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: The Tanah Hitu Kingdom is located on Ambon Island, precisely in Leihitu District, Central Maluku Regency, Maluku Province, Indonesia. It is called the Tanah Hitu Kingdom because it is located in the Leihitu area. When the kingdom still existed, the area was called Tanah Hitu. Now, the name Tanah Hitu no longer exists, what exists is Leihitu District which is sometimes usually called Jazirah Leihitu.Purposes of Devotion: Through mentoring activities, it is hoped that participants will understand the creation/drafting of State Regulations regarding the management of marine resources in Wakal State, as a very important form of management of coastal natural resources in Hitu State, Leihitu District, Central Maluku Regency. Method of Devotion: Through mentoring activities, it is hoped that participants will understand the creation/drafting of State Regulations regarding the management of marine resources in Wakal State, as a very important form of management of coastal natural resources in Hitu State, Leihitu District, Central Maluku Regency.Results of the Devotion: One characteristic that is the same in Maluku is the natural resource management system which is based on the principle of mutual benefit and reciprocity (reciprocity) to maintain the balance of the natural environment called sasi. Sasi is a customary law provision that strictly prohibits anyone from taking anything from the natural surroundings, land or sea, at a certain time in order to ensure its preservation.